Lower FSH With Normal Fertility in Male Mice Lacking Gonadotroph Kisspeptin Receptor - Ma, Yaping; Awe, Olubusayo; Radovick, Sally; Yang, Xiaofeng; Divall, Sara; Wolfe, Andrew; Wu, Sheng (Frontiers in Physiology, 2022)
The kisspeptin receptor, crucial for hypothalamic control of puberty and reproduction, is also present in the pituitary gland. Its role in the pituitary gland is not defined. Kisspeptin signaling via the Kiss1r could potentially regulate reproductive function at the level of pituitary gonadotrope. Using Cre/Lox technology, we deleted the Kiss1r gene in pituitary gonadotropes (PKiRKO). PKiRKO males have normal genital development (anogenital distance WT: 19.1±0.4 vs PKiRKO: 18.5±0.4mm), puberty onset, testes cell structure on gross histology, normal testes size, and fertility. PKiRKO males showed significantly decreased serum FSH levels compared to WT males (5.6±1.9 vs 10.2±1.8ng/ml) with comparable LH (1.1±0.2 vs 1.8±0.4ng/ml) and testosterone levels (351.8±213.0 vs 342.2±183.0 ng/dL). PKiRKO females have normal puberty onset, cyclicity, LH and FSH levels and fertility. Overall, these findings indicate that absence of pituitary Kiss1r reduces FSH levels in male mice without affecting testis function. PKiRKO mice have normal reproductive function in both males and females.